Perceiving Fixed or Flexible Meaning: Toward a Model of Meaning Fixedness and Navigating Occupational Destabilization - Jiang, Winnie Yun; Wrzesniewski, Amy (Administrative Science Quarterly, 2023)
This article examines individuals’ cognitive, emotional, and behavioral responses to the destabilization of their occupations, how their responses differ, and why. We focus on the context of journalism, an occupation undergoing severe destabilization in the U.S. and seen as deeply meaningful by many of its incumbents. Drawing on two waves of interviews with 72 unemployed or former newspaper journalists, conducted over five months, and additional interviews with 22 others, we identified two sets of responses, each characterized by distinctive cognitive, emotional, and behavioral patterns. Building on these findings, we developed the construct of “meaning fixedness” to capture the extent to which individuals view the meaning of the different components of their work to be fixed within one occupational context or flexible across different occupations. We found that participants held different interpretations of journalism’s destabilization and assessments of how portable their work components were to other occupational contexts: flexible-meaning perceivers generally engaged in actions to reinvent their career, while fixed-meaning perceivers engaged in actions to persist in journalism with the hope that their occupation could be restored. Our findings culminate in a model of meaning fixedness and how it shapes individuals’ navigation of occupational destabilization. This research uncovers an individual-level perception that has the potential to shape the varied responses to occupational changes observed in prior research, contributing to the literatures on occupations, the meaning of work, and role transitions.